COMPOSITION AND AGE OF THE PENCHENGA LINEAR CARBONATITE COMPLEX, YENISEI RANGE - Vrublevskii V.V.; Pokrovskii B.G.; Zhuravlev D.Z.; Anoshin G.N. (My University, 2003)
The Penchenga linear fenite-carbonatite complex is situated in the Tatarka fault zone of the Yenisei Range. It is made up of a series of closely spaced sheetlike bodies of magnesiocarbonatite surrounded by contact metasomatic aureoles and has no spatial connection with occurrences of alkaline magmatism. Problems of the age, genesis, and sources of the complex are addressed on the basis of new mineralogical, geochemical, and isotopic data. The Sm-Nd isochron age of the carbonatites was estimated as 672 ± 93 Ma (εNd = 5.4 ± 1.1 and MSWD = 8.1) and is compatible with the K-Ar and Rb-Sr isotopic dating. This allows us to connect carbonatite formation with the Late Riphean epoch of rift activation in the Baikalian sequences of the folded framing of the Siberian craton. The low values of 87Sr/86Sr672 = 0.70229-0.70235 and high εNd672 = 5.1-5.5 suggest a depleted mantle source of the magnesiocarbonatites. Their major rock-forming element ratios, Mg/(Mg + Fe) ∼ 0.7-0.9, Ca/(Ca + Mg) ∼ 0.6-0.7, and SiO2 ∼ 2-7 wt %, are not much different from those of alkali-rich dolomite liquids obtained in experiments on the partial melting of mantle peridotites. However, the stable isotope characteristics suggest a complex evolution of the carbonatite system in the upper part of the lithosphere. The relatively high values of δ13C (from -5.9 to -1.8‰) and δ18O (8.0-14.1‰) in dolomite, the low values of δ18O in magnetite (from -0.3 to -0.5‰) and pyrochlore (from -2.8 to -3.2‰) atypical of unaltered magmatic carbonatites, the considerable variations in the oxygen and hydrogen isotopic compositions of biotite (δ18O = 3.87.1‰ and δD from -30 to -93‰) and amphibole (δ18O = 3.1-5.0‰ and δD from -98 to -154‰), and the enrichment of accessory pyrrhotite in δ34S (δ34S from -0.8 to 9.2‰) led us to the conclusion that the carbonatite of the Penchenga complex were affected by high-temperature (350-500°C) metasomatic alterations, which involved atmospheric fluids.